1995
DOI: 10.1029/94jd03003
|View full text |Cite
|
Sign up to set email alerts
|

Ozone absorption spectroscopy in search of low‐lying electronic states

Abstract: A spectrometer capable of detecting ozone absorption features 9 orders of magnitude weaker than the Hartley band has been employed to investigate the molecule's near‐infrared absorption spectrum. At this sensitivity a wealth of information on the low‐lying electronically excited states often believed to play a role in atmospheric chemistry is available in the form of vibrational and rotational structure. We have analyzed these spectra using a combination of digital filtering and isotope substitution and find e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 42 publications
9
62
1
Order By: Relevance
“…Woywod et al calculated the spectrum using their surfaces, which we use here, and showed that it agreed very well with the experimental one of Mauersberger et al [34].…”
Section: The Absorption Spectrumsupporting
confidence: 70%
“…Woywod et al calculated the spectrum using their surfaces, which we use here, and showed that it agreed very well with the experimental one of Mauersberger et al [34].…”
Section: The Absorption Spectrumsupporting
confidence: 70%
“…In 1992, Braunstein and Pack [18] proposed to assign the main part of the Wulf band as a 3 A 2 -X 1 A 1 transition. This was confirmed in 1994 [19] and experimentally by Anderson and Mauersberger [20] in 1995, using absorption spectra of the 16 O 3 and 18 O 3 isotopologues at low resolution (4 cm À1 ). From 1996 to 1998, Bouvier et al [21,22] and Abel et al [23] recorded the 3 A 2 (0 0 0)-X 1 A 1 (0 0 0) and 3 A 2 (0 1 0)-X 1 A 1 (0 0 0) bands at high resolution allowing partial rotational assignments, line width measurements and the determination of the 3 A 2 (0 0 0)-X 1 A 1 (0 0 0) band origin of 16 O 3 at 9553.0 ± 0.1 cm À1 [22].…”
Section: Introductionsupporting
confidence: 58%
“…We consider next the possible explanation of the enrichment in terms of low-lying electronic states, and focus on coupling via spin-orbit terms, although other spin and/or rovibronic couplings can also occur. There are several lowlying triplet states, barely thermally accessible, [74][75][76][77][78][79][80] except at large values of the asymmetric stretching coordinate q 3 , where some 27 electronic states approach each other in energy. These states could increase the density of reactive states.…”
Section: Discussionmentioning
confidence: 99%